Αχελομορφωθ: magistrates of Akarnania. A Reconsideration of the iconographic fluctuations on Akarnanian federal coinage - Molinari, Dr Nicholas J. (KOINON: The International Journal of Classical Numismatic Studies, 2020)
There is an interesting iconographic phenomenon that scholars witness on the 3rd to 2nd century BC coinage of the Akarnanian Federation: ‘Acheloios’ appears either with or without a beard, and this change is unprecedented in the vast body of coinage featuring him throughout the Greek world, where he is always bearded. What accounts for this bold change? Is the beardless version some way of recognizing a specific dimension to river god worship, the beardless (youthful?) Acheloios somehow connected with koureion rituals, or something of that sort? A similar explanation was suggested in the Sicilian context to explain the difference between bearded man-faced bulls and horned, beardless male heads. Or, perhaps the variation reflects the different physical states of the river at different times, as I tentatively suggested in POTAMIKON concerning some rare bronze issues from nearby Ambrakia (which copy the types under discussion), again following the rationale others have used to explain the aforementioned differentiation in river god iconography elsewhere. In this case, the beardless Acheloios might be indicative of the river when it is calm, at its origin, whereas the bearded Acheloios represents the river downstream in all its silver-eddying glory. Or, perhaps the differentiation simply reflects a change in taste over the years, with more artists preferring the beardless version in the second half of the 3rd century and beyond.